2020
DOI: 10.3390/cells9071676
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Immune Activation Sensitizes Male Offspring Rats to Lipopolysaccharide-Induced Microglial Deficits Involving the Dysfunction of CD200–CD200R and CX3CL1–CX3CR1 Systems

Abstract: Early life challenges resulting from maternal immune activation (MIA) may exert persistent effects on the offspring, including the development of psychiatric disorders, such as schizophrenia. Recent evidence has suggested that the adverse effects of MIA may be mediated by neuron–microglia crosstalk, particularly CX3CL1–CX3CR1 and CD200–CD200R dyads. Therefore, the present study assessed the behavioural parameters resembling schizophrenia-like symptoms in the adult male offspring of Sprague-Dawley rats that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 136 publications
3
32
0
Order By: Relevance
“…Thus, the negative correlation between novelty-related behaviour, immobility, and climbing time in the FST, which has been postulated by some authors [ 83 , 84 ], has been confirmed. Our present results are consistent with previously published data from the MIA model induced by the administration of the bacterial endotoxin lipopolysaccharide (LPS) [ 85 ] as well as with the results of other authors obtained in neurodevelopmental models of schizophrenia [ 86 ]. These observations positively validate the Poly I:C MIA model in the context of the presence of positive symptoms in animals, which can be compared with the psychomotor agitation present in some schizophrenic patients [ 87 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, the negative correlation between novelty-related behaviour, immobility, and climbing time in the FST, which has been postulated by some authors [ 83 , 84 ], has been confirmed. Our present results are consistent with previously published data from the MIA model induced by the administration of the bacterial endotoxin lipopolysaccharide (LPS) [ 85 ] as well as with the results of other authors obtained in neurodevelopmental models of schizophrenia [ 86 ]. These observations positively validate the Poly I:C MIA model in the context of the presence of positive symptoms in animals, which can be compared with the psychomotor agitation present in some schizophrenic patients [ 87 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our previous study, we demonstrated that elevated IL-6 levels preceded the manifestation of schizophrenia-like disturbances [ 130 ]. Additionally, acute IL-6 treatment was shown to trigger a deficit in sensorimotor gating in mice [ 19 ], while in Sprague-Dawley rats in the LPS-induced MIA model, elevated Il-6 expression participated in the manifestation of the PPI deficit, negative regulation of the CD200-CD200R axis, and microglia priming [ 85 ]. Based on the mentioned data, the time of the tests performed after applying the “second hit” could have influenced the rate of transcription and translation processes as well as the insufficient increase in the level of Il-6 and the lack of expected behavioural effects in offspring with “primed microglia”.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the equipoise between IL-10 induction and the amount of pro-IL1β potentially determines the final level of IL-1β [ 45 ]. IL-10 may also exert an anti-inflammatory effect through the fractalkine receptor (CX3CR1), which is mainly expressed in microglial cells [ 46 , 47 ]. Consistent with the results reported by Cunha et al [ 48 ], in the present study, we observed that LPS diminishes Cx3cr1 expression, but only in WT cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Some chemokines (underlined here) that are altered in schizophrenia can bind to multiple receptors and they all act through increasing calcium transients. Based on [ 10 , 11 , 261 , 264 , 267 , 268 , 269 , 275 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 ].…”
Section: Figurementioning
confidence: 99%